Multi-omics approaches to understand pathogenicity during potato early blight disease caused by Alternaria solani - Li, Qing; Feng, Yan; Li, Jianmei; Hai, Yang; Si, Liping; Tan, Chen; Peng, Jing; Hu, Zuo; Li, Zhou; Li, Canhui; Hao, Dahai; Tang, Wei (Frontiers in Microbiology, 2024)
Potato early blight (PEB), a foliar disease of potato during the growing period, caused by Alternaria sp., is common in major potato-producing areas worldwide. Effective agents to control this disease or completely resistant potato varieties are absent. Large-scale use of fungicides is limited due to possibility of increase in pathogen resistance and the requirements of ecological agriculture. In this study, we focused on the composition and infection characteristics of early blight pathogens in Yunnan Province and screened candidate pathogenesis-related pathways and genes. We isolated 85 strains of Alternaria sp. fungi from typical early blight spots in three potato-growing regions in Yunnan Province from 2018 to 2022, and identified 35 strains of Alternaria solani and 50 strains of Alternaria alternata by morphological characterization and ITS sequence comparison, which were identified as the main and conditional pathogens causing early blight in potato, respectively. Scanning electron microscope analysis confirmed only A. solani producing appressorium at 4 h after inoculation successfully infected the leaf cells. Via genome assembly and annotation, combine transcriptome and proteomic analysis, the following pathogenicity-related unit, transcription factors and metabolic pathway were identified: (1) cell wall-degrading enzymes, such as pectinase, keratinase, and cellulase; (2) genes and pathways related to conidia germination and pathogenicity, such as ubiquitination and peroxisomes; and (3) transcription factors, such as Zn-clus, C2H2, bZIP, and bHLH. These elements were responsible for PEB epidemic in Yunnan.